THE ATTITUDES OF HEALTHCARE PROFESSIONALS TOWARDS NURSE–PHYSICIAN COLLABORATION - Nasser Hussain Alyami 1, Ibrahim Mohammed Alshaiban 2, Ahmed Mohammed Saber 3, Eyad Ahmed Ali Alzahrani 4, Sami Abdullah Mesfer Alghamdi 5, Mohammed Fares Hadi Alyami 6, Mohammed Abdullah Zaher Alfaify 7, ‏Mohmmad Rahim Algharawi 8, (Chelonian Research Foundation, 2022)
Aims: This study aims to investigate the perceptions and attitudes of healthcare professionals, particularly focusing on the nurse-physician collaboration and satisfaction levels with the quality of collaboration in clinical settings. Design: A descriptive comparative study design was utilized to assess the attitudes of 338 participants, including 158 internship nurses, 139 staff nurses, and 41 physicians. Participants were selected from intensive care units, surgical departments, and medical departments. Methods: Data was collected using two instruments: a socio-demographic data sheet and the Jefferson Scale of Attitude towards Nurse-Physician Collaboration (JSANPC), which comprises 15 items across four dimensions. Results: The study revealed that internship nurses expressed a high level of dissatisfaction (38.6%) regarding the quality of collaboration between nurses and physicians compared to staff nurses and physicians. Conversely, physicians reported a higher satisfaction level (61%) with the collaboration between themselves and nurses. Staff nurses exhibited a significantly positive attitude (mean score: 48.45 (4.03)) towards nurse-physician collaboration compared to physicians and internship nurses. Conclusion: The findings highlight that internship nurses are generally dissatisfied with the level of collaboration between nurses and physicians in clinical settings. Keywords: collaboration, healthcare professionals, internship nurses, staff nurses, physicians